Reconstruction of Zakah Governance in Indonesia (Review on the No. 23 Year 2011) - Budi Santoso, Cahyo; Nizarul Alim, Mohammad; Riyadi, Slamet (International Journal of Engineering and Technology, 2018)
The issuance of Law Number 23 Year 2011 on the Management of Zakat changed the paradigm of zakat management in Indonesia. The purpose of this study is to assess the governance of zakat based on zakat regulation. The content zalcat content analysis approach shows that BAZNAS has two major roles, namely the coordinator and operator. Supervision is an important element in zalcat governance, currently the state plays a role in supervising the aspects of sharia only [this is done by the Ministry of Religious Affairs] while the supervision on financial management has not been done by the Financial Services Authority [OJK]. Supervision over zakat governance by OJK should be a necessity considering the zakat fund managed by amil zakat nationally more than 3 trillion Rupiah.Â Â